From Ca2+ dysregulation to heart failure: β-adrenoceptor activation by RKIP postpones molecular damages and subsequent cardiac dysfunction in mice carrying mutant PLNR9C by correction of aberrant Ca2+-handling - Brand, Theresa; Baumgarten, Bettina Tanitha; Denzinger, Sabrina; Reinders, Yvonne; Kleindl, Miriam; Schanbacher, Constanze; Funk, Florian; Gedik, Nilgün; Jabbasseh, Mahmood; Kleinbongard, Petra; Dudek, Jan; Szendrödi, Julia; et al. (Pharmacological research, 2024)
Impaired cardiomyocyte Ca2+ handling is a central hallmark of heart failure (HF), which causes contractile dysfunction and arrhythmias. However, the underlying molecular mechanisms and the precise contribution of defects in Ca2+-cycling regulation in the development of HF are still not completely resolved. Here, we used transgenic mice that express a human mutation in the cardiomyocyte Ca2+-regulator phospholamban (PLNR9C-tg) causing severe HF due to a reduction in Ca2+ reuptake into the sarco(endo)plasmic reticulum (SR). PLNR9C-induced HF is a rapidly progressing condition characterized by prominent Ca2+ cycling and relaxation defects and premature death of mutation carriers. We found that endoplasmic reticulum (ER) and mitochondrial function are affected even before transition to overt HF. Early correction of aberrant Ca2+ cycling by cardiac expression of the Raf kinase inhibitor protein (RKIP), an endogenous activator of β-adrenoceptors (βAR), delayed the cellular alterations, functional failure and prolonged lifespan. Our study highlights the importance of early and persistent correction of Ca2+ dynamics, not only for excitation/contraction coupling, but also for the prevention of rather irreparable events on cardiac energetics and ER stress adaptations. The latter may even impede with later onset of Ca2+-related therapeutic interventions and should gain more focus for HF treatment.
Im Titel steht "2+" beide Male und "R9C" in PLNR9C hochgestellt
Gesehen am 25.07.2025